Meningkatkan Kemampuan Pengenalan Kosakata Bahasa Arab Melalui Media Bithoqotu Ash-Shuroh pada Anak Usai Dini - Fiharti, Pebri; Istikomah, Istikomah; Mabruri, Mabruri (Institut Agama Islam Yasni Bungo, 2025)
The aim of this research is to determine the process of ability to recognize Arabic vocabulary using Bithoqotu Ash-Shuroh media among group B children in Raudhatul Athfal Ar-Rohmah, at Pulau Pekan Village, Bungo Regency. This type of research is classroom action research. This research procedure uses the Stephen Kemmis and Robin Mc. Taggart Model. This research was conducted over two cycles, each cycle consisting of 2 meetings. This research, data collection techniques use observation and documentation techniques which aim to obtain observational data on the ability to recognize Arabic vocabulary. The research subjects were 10 group B children, consisting of 4 girls and 6 boys. Before taking action with Bithoqotu Ash-Shuroh Media, children's ability to recognize Arabic vocabulary was still classified as starting to develop, namely 44%. Therefore, it is necessary to take action using Bithoqotu Ash-Shuroh Media, in cycle I. The ability to recognize Arabic vocabulary for group B children increased to 59% but was still classified as starting to develop and increased in cycle II, namely 82% with the criteria of developing very well and has met the criteria for success of the action. Based on the results of the study, it can be concluded that the bithoqotu ash-shuroh media has been proven to improve the ability to recognize Arabic vocabulary in group B children at Raudhatul Athfal Ar-Rohmah.